Improved procedure for a high-yield recovery of enzymatically active recombinant calf chymosin from Escherichia coli inclusion bodies - Tichý, P J; Kaprálek, F; Jecmen, P (Protein expression and purification, 1993)
The high-yield recovery of enzymatically active recombinant calf chymosin from Escherichia coli inclusion bodies was achieved by optimization of solubilization and renaturation conditions. The solubilization was carried out in 8 M urea at various pHs, at various temperatures, and for various periods of time. The following values were found optimal: 1 h at 31 degrees C, pH 10.4. For successful correct refolding of solubilized prochymosin molecules it was found to be necessary to dilute the solution into an alkaline buffer (pH 10.7) in such a way that the final concentration of urea did not exceed 0.32 M and that of protein 0.275 mg/ml. Our optimized procedure gives about eight times higher yields of enzymatically active chymosin than the current published methods.
Keywords: Solubility; Animals; Cattle; Temperature; chromatografie iontoměničová; koncentrace vodíkových iontů; Recombinant Fusion Proteins; Chymosin; Hydrogen-Ion Concentration; močovina; teplota; Cloning, Molecular; zvířata; rozpustnost; chymosin; Urea; Escherichia coli; klonování DNA; denaturace proteinů; Chromatography, Ion Exchange; Protein Denaturation; skot; rekombinantní fúzní proteiny